Symmetry of disciform scars in bilateral age-related macular degeneration. - Lavin, M J (1991)
The size of the final macular scar in subretinal neovascularisation (SRNV) is one of the most important determinants of final visual function in patients with subfoveal disease. We studied patients with bilateral macular scars from age-related subretinal neovascular membranes retrospectively in order to determine whether or not fellow eyes behave similarly. We found a significant correlation between eyes in terms of final scar size (r = 0.50, p less than 0.01). We found that 50% of fellow eyes with large macular scars (greater than 3 x 10(6) microns2) had similar sized lesions, while only 16% of fellow eyes with small macular scars (less than 0.5 x 10(6) microns2) had large scars (p less than 0.01). We discuss the significance of these findings in relation to the pathogenesis of subretinal neovascular membranes, and their implications for treatment.